Analisis Pengaruh Indeks Pembangunan Manusia (IPM), Tenaga Kerja Sektor Pertanian, Luas Panen Padi terhadap Produk Domestik Regional Bruto (PDRB) Sektor Pertanian - Parkah, Diana Indah; Huda, Syamsul; Perdana, Putra (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to analyze the influence of the Human Development Index (HDI), agricultural sector workforce, and rice harvest area on the Gross Regional Domestic Product (GRDP) of the agricultural sector in Lamongan Regency, Jember Regency, Ngawi Regency, and Banyuwangi Regency for the period 2011-2022 . This research uses secondary data in the form of time series (annual) from the Central Statistics Agency (BPS) of East Java Province. This type of research is quantitative research using linear regression analysis of panel data. The model in this research uses the fixed effect model (FEM). The research results show that simultaneously the HDI variables, agricultural sector labor, rice harvest area have a positive effect on the agricultural sector's GRDP. Meanwhile, partially the rice harvest area variable has no effect on the GDP of the agricultural sector in Lamongan Regency, Jember Regency, Ngawi Regency and Banyuwangi Regency in 2011-2022.